Blastocystis subtyping and its association with intestinal parasites in children from different geographical regions of Colombia (2017)
Blastocystis is a common enteric protist colonizing probably more than 1 billion people with a large variety of non-human hosts. Remarkable genetic diversity has been observed, leading to the subdivision of the genus into multiple subtypes (ST), some of which are exclusively found in non-human hosts. The aim of this study was to determine the distribution of Blastocystis STs/18S alleles in symptomatic (abdominal pain, anal pruritus, diarrhea, headache, nauseas and/or vomit) and asymptomatic children from nine geographical regions of Colombia. A total of 2026 fecal samples were collected as part of a national survey to estimate the frequency of intestinal parasites in children. A set of 256 samples that were Blastocystis positive was finally selected. The samples were submitted to DNA extraction, Real Time PCR and sequencing using Blastocystis-specific primers targeting the small subunit rRNA gene for ST identification. DNA of Ascaris lumbricoides (16.4%), Trichuris trichiura (8.2%), hookworms (Necator americanus/Ancylostoma duodenale) (7.3%), Giardia duodenalis (23.1%), Entamoeba complex (82%), Entamoeba coli (55%), Hymenolepis nana (0.8%), Endolimax nana (33.2%) and Neobalantidium coli (2.7%) was detected in the Blastocystispositive samples. We detected ST1 (21.4%), ST2 (19.5%), ST3 (55.5%), ST4 (0.8%), ST6 (2%) and ST7 (0.8%); alleles 1, 2, 4, 81, 82 and 83 for ST1; alleles 9, 11, 12, 15, 67, 71 and 73 for ST2; alleles 34, 36, 38, 45, 49, 55, 134 and 128 for ST3; allele 42 for ST4; allele 122 for ST6, and allele 142 for ST7. Further studies implementing high-resolution molecular markers are necessary to understand the dynamics of Blastocystis transmission and the role of this Stramenopila in health and disease. © 2017 Ramírez et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.